2019
DOI: 10.1038/s41526-019-0075-2
|View full text |Cite
|
Sign up to set email alerts
|

Supplying a pharmacy for NASA exploration spaceflight: challenges and current understanding

Abstract: In order to maintain crew health and performance during long-duration spaceflight outside of low-Earth orbit, NASA and its international partners must be capable of providing a safe and effective pharmacy. Given few directed studies of pharmaceuticals in the space environment, it is difficult to characterize pharmaceutical effectiveness or stability during spaceflight; this in turn makes it challenging to select an appropriate formulary for exploration. Here, we present the current state of literature regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 56 publications
0
90
0
2
Order By: Relevance
“…In some animal studies, spaceflight seems to change the activity of cytochrome P450 enzymes. The results are, however, inconsistent, perhaps reflecting methodological differences …”
Section: Crystal Clearmentioning
confidence: 92%
See 1 more Smart Citation
“…In some animal studies, spaceflight seems to change the activity of cytochrome P450 enzymes. The results are, however, inconsistent, perhaps reflecting methodological differences …”
Section: Crystal Clearmentioning
confidence: 92%
“…But some other organisms show increased susceptibility. Biofilms grown in space show a different structure and are more complex than those on Earth . Experiments in microgravity help identify the regulatory pathways and genes driving changes in virulence, potentially offering new targets for treatments and vaccines against, for example, Salmonella gastroenteritis, methicillin‐resistant Staphylococcus aureus (MRSA) and Streptococcus pneumonia…”
Section: Killer Bugs From Spacementioning
confidence: 99%
“…Most recently, enoxaparin and apixaban were used for treating jugular venous thrombosis in an astronaut onboard the ISS [4]. The efficacy and safety of these treatments are largely unknown, and it has been suggested that some medications may be less effective than expected [5]. However, in addition to pharmacokinetics and pharmacodynamics, the nature of disease itself (e.g.…”
Section: Medication Usage In Spacementioning
confidence: 99%
“…I slike tilfeller bør spesialisten på bakken inneha romfartmedisinsk kompetanse, inkludert innsikt i de fysiologiske og anatomiske endringene som astronautene gjennomgår i vektløshet. Det er også bekreftet gjennom flere studier at farmakokinetiske og farmakodynamiske egenskaper til mange medikamenter er annerledes i rommet (11), og man kan ikke nødvendigvis benytte samme prinsipper og doser som på Jorden. Dersom hendelsen er svaert alvorlig, kan astronauten evakueres fra den internasjonale romfartstasjonen til Jorden med Sojus-fartøyet.…”
Section: Akuttmedisinsk Beredskapunclassified